The Effect of PC6 Acupressure on Nausea and Vomiting in First Trimester Pregnant Women at PMB Y Purwakarta in 2024 - Aini, Qurotul ‘; Basri, Sherlyani Desianti (CV. Publikasi Indonesia, 2025)
Nausea and vomiting of pregnancy (NVP) in the first trimester remain common and can compromise maternal comfort and nutritional intake, warranting simple, safe, non-pharmacological interventions. This study aimed to analyze the effect of Pericardium-6 (P6) acupressure on the frequency of NVP among first-trimester pregnant women at PMB Y Purwakarta in 2024. A pre-experimental one-group pretest–posttest design with consecutive sampling was used (n = 30). Most respondents were aged 20–35 years (93.3%), multiparous (60%), had high-school education (80%), and were not employed (83.3%). NVP severity was measured using a standardized instrument. The research method used the experimental Quasy method. The design used in this study is one group pre-posttest design without control group. From the results of the study, it was found that the Univariate Analysis was obtained based on the highest age of the mother, which is 20-35 years old 2. The frequency of nausea and vomiting before the intervention was mostly nausea and moderate vomiting as many as 19 people (63.3%). The frequency of nausea and vomiting after the intervention was mostly nausea and mild vomiting (100%). There was an effect of P6 acupressure massage on the frequency of nausea and vomiting in pregnant women in the 1st trimester at PMB Y Purwakarta in 2024 with p = 0.000. There is an effect of P6 acupressure massage on the frequency of nausea and vomiting in pregnant women in the 1st trimester at PMB Y Purwakarta in 2024.